US medical school curriculum on opioid use disorder—a topic review of current curricular research and evaluation of winning student-designed opioid curricula for the 2021 Coalition on Physician Education in Substance Use Disorders curricular competition - Cao, Ling; Van Deusen, Jennifer (Frontiers in Pain Research, 2023)
The opioid crisis in the US severely affected and continues to affect population's health. The opioid crisis was in part fueled by inadequate pain management, which is in part due to the inadequate education in both pain and opioid use disorder (OUD) for health care professionals. In 2021, the Coalition on Physician Education in Substance Use Disorders (COPE) organized a curricular competition soliciting US medical students-designed OUD-related curricula. Twelve winning curricula were identified. Here, we first conducted a topic review regarding current US medical school OUD curricula. Then we evaluated the COPE winning curricula and compared them to the curricula identified in the topic review. For the topic review, ten relevant databases were searched up to December 31, 2021 using a combination of pre-determined keywords. Total of 25 peer-reviewed articles were selected based on the pre-determined criteria, which included 5 articles describing opioid curricular development at the state level (AZ, CA, MA, PA, and RI), 17 research articles evaluating a curriculum developed in a single institution, 2 literature reviews, and 1 article detailing curricular development and validation processes in a single institution. Although vary in organizations and formats, state-level curricula were comprehensive and could be adopted by other states or institutions with necessary local issue-based modifications. Faculty development and critical resources were major challenges for curricular implementation. The 17 research articles exhibited good scientific quality (Medical Education Research Study Quality Instrument (MERSQI) score = 11.94 ± 2.33 (maximal score = 18)). All research articles reported to some extent, the success of respective curriculum, in improving students' knowledge in and/or attitude towards OUD, based on primarily pre- and post- comparisons. Compared to these published curricula, winning students-designed curricula had more specific focuses, diverse learning activities, and varieties in assessment methods. For all curricula, long-term evaluations were lacking. Except for the state level curricula, majority of the other curricula did not emphasize specifically on chronic pain education or the biopsychosocial approach. Interprofessional education approach was also lacking. Our topic review and curricular evaluation highlighted the needs for integrating OUD and chronic pain medical curricula, developing long-term assessment tools, and more OUD curriculum research overall.